The Role of Brand Attachment and Brand Trust on Customer Retention with Brand Loyalty as Mediating Variable: Evidence from Bank BJB Medan Branch - Muhammad Maulana Ishaq; Muhammad Dharma Tuah Nasution; Slamet Widodo (Ridwan Institute, 2026)
The increasing competition in the banking industry has encouraged financial institutions to strengthen customer relationships in order to maintain long-term customer retention. In this context, brand attachment and brand trust are considered important determinants in shaping brand loyalty and customer retention. This study aims to examine the role of brand attachment and brand trust on customer retention with brand loyalty as a mediating variable at Bank BJB Medan Branch. The research employed a quantitative approach using a cross-sectional survey design. Data were collected from 154 active customers selected through purposive sampling. The analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The findings reveal that brand trust has a strong and significant effect on brand loyalty, while brand attachment has a weaker but still significant influence on loyalty. Furthermore, brand loyalty significantly affects customer retention. The mediation analysis indicates that brand loyalty successfully mediates the relationship between brand trust and customer retention, whereas the mediating effect between brand attachment and customer retention is not significant. The results demonstrate that trust plays a more dominant role than emotional attachment in maintaining customer relationships within the banking sector. In conclusion, Bank BJB should prioritize trust-building strategies through transparency, service reliability, and customer-oriented communication to strengthen loyalty and improve long-term customer retention.